Long term outcome of antiviral therapy in patients with hepatitis B associated decompensated cirrhosis - Ju, Young-Cheol; Jun, Dae-Won; Choi, Jun; Saeed, Waqar Khalid; Lee, Hyo-Young; Oh, Hyun-Woo (World journal of gastroenterology : WJG, 2018)
To investigate survival rate and incidence of hepatocellular carcinoma (HCC) in patients with decompensated cirrhosis in the antiviral era. We used the Korean Health Insurance Review and Assessment. Korea's health insurance system is a public single-payer system. The study population consisted of 286871 patients who were prescribed hepatitis B antiviral therapy for the first time between 2007 and 2014 in accordance with the insurance guidelines. Overall, 48365 antiviral treatment-naïve patients treated between 2008 and 2009 were included, and each had a follow-up period ≥ 5 years. Data were analyzed for the 1 decompensated chronic hepatitis B (CHB) and treatment-naïve patients ( = 7166). The mean patient age was 43.5 years. The annual mortality rates were 2.4%-19.1%, and 5-year cumulative mortality rate was 32.6% in 1 decompensated CHB treatment-naïve subjects. But the annual mortality rates sharply decreased to 3.4% (2.4%-4.9%, 2-5 year) after one year of antiviral treatment. Incidence of HCC at first year was 14.3%, the annual incidence of HCC decreased to 2.5% (1.8%-3.7%, 2-5 year) after one year. 5-year cumulative incidence of HCC was 24.1%. Recurrence rate of decompensated event was 46.9% at first year, but the annual incidence of second decompensation events in decompensated CHB treatment-naïve patients was 3.4% (2.1%-5.4%, 2-5 year) after one year antiviral treatment. 5-year cumulative recurrence rate of decompensated events was 60.6%. Meanwhile, 5-year cumulative mortality rate was 3.1%, and 5-year cumulative incidence of HCC was 11.5% in compensated CHB treatment-naïve patients. Long term outcome of decompensated cirrhosis treated with antiviral agent improved much, and incidence of hepatocellular carcinoma and mortality sharply decreased after one year treatment.